Implied Relevance in Panji Gumilang's Violation of Maxim Relevance in Kick Andy Interview: A Cognitive Pragmatics Study - Panji, Artha Nur Restia; Lukman, Fahmy; Ardiati, Riza Lupi (Lensa: Kajian Kebahasaan, Kesusastraan, dan Budaya, 2024)
Panji Gumilang and his educational institution, Al-Zaitun, have been the subject of much discussion in the last few months because of their heresy case. In the interview on the Kick Andy Talk Show, many of his utterances were not contextualised with the interviewer's questions. This research aims to analyse the meaning of ‘convoluted’ Impliedature contained in the Violation of Cooperation Principle Maxim Relevance of Panji Gumilang's speech in Kick Andy interview based on Grice Theory and Relevance Theory. The research data is in the form of pieces of AS Panji Gumilang's speech that are irrelevant to Andy's questions so that they imply implicature meaning. The research data were collected through observation technique and documentation technique. While the data source of this research is obtained through the video interview of the Kick andy television program on the Metro TV youtube channel entitled ‘Gonjang-Ganjing Al-Zaitun’ uploaded on 6 June 2023. The method of data analysis in this study applies the pragmatic commensurate analysis method with the basic technique of sorting out the determining elements and the advanced technique of comparative equating. The data presentation method is done descriptively with the help of infromal words. The result of this research shows that Panji's violation of maxim of relevance represents the intention or information that he wants to avoid and hide against the question from the interviewer Andy F Noya. The hidden information of Panji's speech is analysed through the premises of implicature in the process of interpreting the relevance of the conversation based on the knowledge and cognition experience between the two members of the conversation.